2012
DOI: 10.3171/2012.9.spine111021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of safety and stability of C-2 pars and pedicle screws for atlantoaxial fusion: meta-analysis and review of the literature

Abstract: Object Some centers report a lower incidence of vertebral artery (VA) injury with C-2 pars screws compared with pedicle screws without sacrificing construct stability, despite biomechanical studies suggesting greater load failures with C-2 pedicle screws. The authors reviewed published series describing C-2 pars and pedicle screw implantation and atlantoaxial fusions and compared the incidence of VA injury, screw malposition, and successful atlantoaxial fusion with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 74 publications
1
26
0
4
Order By: Relevance
“…The direction of the screw is 15 -30 medial and 20 -25 cephalad. Although a biomechanical study has shown that C2 pedicle screws have twice the pullout strength of C2 pars screws [68], the clinical results of the two fixation techniques are similar [69]. Both the C2 pedicle screw and C2 pars screw are widely used for screw-rod system fixation of C1-C2 fusion [69].…”
Section: C2 Pedicle Screw Techniquementioning
confidence: 97%
“…The direction of the screw is 15 -30 medial and 20 -25 cephalad. Although a biomechanical study has shown that C2 pedicle screws have twice the pullout strength of C2 pars screws [68], the clinical results of the two fixation techniques are similar [69]. Both the C2 pedicle screw and C2 pars screw are widely used for screw-rod system fixation of C1-C2 fusion [69].…”
Section: C2 Pedicle Screw Techniquementioning
confidence: 97%
“…30,36 C1-C2TL constructs are commonly used for cases in which contraindications for C1-C2TA and C1LM-C2PS constructs exist, primarily to avoid vertebral artery injury; the reported fusion rate is 92.9%. 30 Elliott et al 10 performed a meta-analysis and found a slightly higher incidence of vertebral artery injury in C1LM-C2PS constructs than in C1LM-C2 pars constructs, with reported fusion rates higher for C1LM-C2PS constructs (97.8%) than for C1LM-C2 pars constructs (93.5%). Given our findings of insufficient biomechanical stabilization of lateral bending by the C1-C2TL construct, clinical studies to compare long-term fusion rates and the incidence of hardware failures to the other constructs may help provide a clinical correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Elliott et al 7 reviewed atlantoaxial grafting options and found no significant difference in fusion rates between allograft and autograft constructs but noted wide variability in the use of autograft, allograft, and bone morphogenetic protein. The study found a 99.7% fusion rate among 652 patients treated with autograft and a 100% fusion rate among 60 patients treated with allograft in 7 studies; however, the majority of these included morselized allografts rather than the structural allograft described in the current study.…”
Section: Discussionmentioning
confidence: 99%